2021
DOI: 10.1177/15353702211034164
|View full text |Cite
|
Sign up to set email alerts
|

Stopping the COVID-19 pandemic in dental offices: A review of SARS-CoV-2 transmission and cross-infection prevention

Abstract: Due to the essential role of dentists in stopping the COVID-19 pandemic, the purpose of this review is to help dentists to detect any weaknesses in their disinfection and cross-contamination prevention protocols, and to triage dental treatments to meet the needs of patients during the pandemic. We used PRISMA to identify peer-reviewed publications which supplemented guidance from the center for disease control about infection control and guidelines for dentists. Dentists must triage dental treatments to meet t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Dental healthcare professionals, including dentists, dental assistants, dental hygienists, and nurses were aware of the high risk of exposure in the early stages of the COVID-19 pandemic [18,19]. The fact is that dentists are at a high risk of contracting COVID-19 from their patients because of its transmission by respiratory droplets and the use of dental handpieces that can generate aerosols [20,21], as well as the physical proximity of their patients [19,22,23]. Understanding the significance of aerosol transmission and its implications in dentistry can facilitate the identification and possible correction of negligence in daily dental practice [24].…”
Section: Introductionmentioning
confidence: 99%
“…Dental healthcare professionals, including dentists, dental assistants, dental hygienists, and nurses were aware of the high risk of exposure in the early stages of the COVID-19 pandemic [18,19]. The fact is that dentists are at a high risk of contracting COVID-19 from their patients because of its transmission by respiratory droplets and the use of dental handpieces that can generate aerosols [20,21], as well as the physical proximity of their patients [19,22,23]. Understanding the significance of aerosol transmission and its implications in dentistry can facilitate the identification and possible correction of negligence in daily dental practice [24].…”
Section: Introductionmentioning
confidence: 99%
“…A German study [ 43 ] reported that an additional measure includes compound daily patient care and patient time required with established infection control protocols are required in the dental operatory. An American study [ 44 ] reported that it is imperative to maintain social distancing and changes of personal protection equipment for every patient. In the present study, more than 80% of the pediatric dentist felt the use of PPE and social distancing is compulsory to avoid cross-contamination of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Dental healthcare professionals -including dentists, dental assistants, dental hygienists and nurses were aware of high risk of exposure in the early stages of COVID-19 pandemic [13,14]. It is known that dentists have a high risk of contracting COVID-19 from their patients because of its transmission by respiratory droplets and the use of dental handpieces that can generate aerosols [15,16] as well as the physical proximity to their patients [14,17,18]. Not all dental practices considered a transmission of SARS-CoV-2 as a real risk for them or their patient.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the widespread anxiety and fear of the devastating health effects of COVID-19, only 61% of dentists have implemented a fundamental modification to their treatment protocols. Facing the highly infectious Omicron strain, as an urgent matter of public health, all dentists must identify the additional steps they can take to prevent the spread of infection [16]. A clinical practice guidelines used in the first year of pandemic might change with a new more infectious variants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation